Penerapan Model Pembelajaran PjBl Berbantuan Simurelay Untuk Meningkatkan Hasil Belajar Siswa di SMKS Raden Paku - Krestanti Anggun Wahyuning; Tri Rijanto; Nur Kholis; Yulia Fransisca (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
The purpose of this study was to determine how effective the use of the PjBL learning model assisted by simurelay, student learning outcomes in the aspects of knowledge, attitudes, and skills after applying the PjBL learning model assisted by simurelay, and student responses to the use of the PjBL learning model assisted by simurelay in the subject of Electric Motor Installation at Raden Paku SMKS. The research was conducted in a Quasi Experimental manner and used a Non-Equivalent Control Group Design. 44 students were used as samples, where they were divided into two sessions. Each with 22 students in the first session and 22 students in the second session. Data were collected using observation, test, and questionnaire techniques. Based on the research, the implementation of PjBL learning assisted by simurelay obtained an average of 95% and the average student activity of 96.3%, which is in the percentage of 81% - 100% included in the very good criteria. The average value of student learning outcomes shows an increase. Where there are 63.6% getting scores above KKTP and 36.4% getting scores below KKTP. The results of the hypothesis research show that the value of Asymp. sig. (2-tailed) = 0.000 <0.05, which indicates that there is a significant difference. The mean N-Gain value of the experimental class = 0.612, which means that the effectiveness of using the simurelay-assisted PJBL learning model is in the medium category and the average percentage value of N-Gain = 61.1%, which represents the “quite effective” category. While in the control class the average value of N-Gain = 0.40, and the average percentage value of N-Gain = 40%, which represents the category “less effective”. Therefore, it can be concluded that the application of the PjBL learning model assisted by simurelay in the category is quite effective in improving the learning outcomes of students in class XI TITL SMKS Raden Paku. In this study, there was a very good response from students after applying the learning model.